INTERNAL WAVES DYNAMICS IN THE LOMBOK STRAIT STUDIED BY A NUMERICAL MODEL - NINING SARI NINGSIH; RIMA RAHMAYANI; SAFWAN HADI; IRSAN S. BROJONEGORO (BRIN, 2008)
A baroclinic 3D hydrodynamic model with the non-hydrostatic approximation called Massachusetts Institute of Technology Global Circulation Model (MIT gcm) has been applied to simulate the generation of internal tidal bores and their disintegration into internal solitary waves in the Strait of Lombok. Numerical simulation have been carried out by incorporating seasonal variations of the stratification of the water body, which exist during the first transitional monsoon, the east monsoon, the second transitional monsoon, and the west monsoon. Our simulation yields the results that the existence of the sill at the southern part of the Lombok Strait, strong tidal flow, and a stratified fluid, play an important role in forming some short of divergence and convergence area as an indication of the birth of internal waves, which are simulated on the both sides of the sill. The simulated results reproduce reasonably well the basic features of internal waves in the Strait of Lombok as captured by the Synthetic Aperture Radar (SAR) from the European Remote Sensing (ERS) satellites ERS 1 and ERS 2, such as a north-south asymmetry, propagation speeds, average amplitudes and wavelengths, and solution packets. Similiar to observations made by National Oceanic and Atmospheric Administration (NOAA) satellites, the simulation results also showed the intrusion of warmwater from thePacific Ocean into the Indian Ocean and the exitence of well-developmed thermal plume at south of the sill. Seasonal variations of interface depth of thermocline and the density difference between the stratified layers influence magnitudes of the amplitudes and wavelengths of the internal waves and solitons, and the distance of thermal plume in the Lombok Strait. It is found that during the monsoon transition periods and the west monson, the amplitudes of internal waves and solitons at the southern part of the strait is apparently larger than those at the northern one, whereas during the east monsoon, the wave amplitudes is large north of the sill than south of it. Meanwhile, the propagation speeds of northward propagating internal solitary waves (0.71-2.67m per s) are stronger than southward propagating ones (0.21-1.53 m per s) throughout the monsoon periods.